Genetic characterizations of Cryptosporidium spp. from children with or without diarrhea in Wenzhou, China: high probability of zoonotic transmission - Wei Zhao; Guangxu Ren; Weiyan Jiang; Long Wang; Jiayang Wang; Zhongying Yuan; Lanzhu Yan; Yongtai Li; Yanbin Sun; Xinjie Xue; Yanyan Jiang; Gang Lu; et al. (BMC Microbiology, 2024)
Abstract Background Cryptosporidium is a highly pathogenic parasite responsible for diarrhea in children worldwide. Here, the epidemiological status and genetic characteristics of Cryptosporidium in children with or without diarrhea were investigated with tracking of potential sources in Wenzhou City, China. Methods A total of 1032 children were recruited, 684 of whom had diarrhea and 348 without, from Yuying Children’s Hospital in Wenzhou, China. Samples of stool were collected from each participant, followed by extraction of DNA, genotyping, and molecular identification of Cryptosporidium species and subtypes. Results Twenty-two of the 1032 (2.1%) children were infected with Cryptosporidium spp. with 2.5% (17/684) and 1.4% (5/348) in diarrhoeic and asymptomatic children, respectively. Four Cryptosporidium species were identified, including C. parvum (68.2%; 15/22), C. felis (13.6%; 3/22), C. viatorum (9.1%; 2/22), and C. baileyi (9.1%; 2/22). Two C. parvum subtypes named IIdA19G1 (n = 14) and IInA10 (n = 1), and one each of C. felis (XIXa) and C. viatorum (XVaA3g) subtype was found as well. Conclusions This is the first research that identified Cryptosporidium in children of Wenzhou, China, using PCR. Identification of zoonotic C. parvum, C. felis, C. viatorum, and their subtypes indicate potential cross-species transmission of Cryptosporidium between children and animals. Additionally, the presence of C. baileyi in children suggests that this species has a wider host range than previously believed and that it possesses the capacity to infect humans.